50 HZ POWER LINE NOISE REDUCTION OF MAGNETOTELLURIC DATA USING NOTCH FILTER - Yoshua Marbun, Adolf
On the last decades, energy demand is extremely increasing along with the human population which makes the economy growth also goes up and encourages the energy use globally. Earth's oil and gas still becomes the pledge of the fulfillment of energy needs. Nevertheless, energy which comes out from fossils is no longer able to fulfill energy demands. Therefore, needed is the role of alternative energies which is environmentally friendly and sufficient to sum up the energy demands. One of them is geothermal energy. Geographically, Indonesia's tectonic predicament supports the alternative energy supply. It is due to Indonesia's ring-of-fire-surrounded country which lies from Sumatera to Nusa Tenggara. The existence of volcanic line becomes the criteria of Indonesia for potentially supplying geothermal system. Magnetotelluric method is one of geophysics methods applied to explore the geothermal system. Magnetotelluric method is a passive geophysics method which uses the natural electromagnetic field to delineate the electrical characteristic of rocks beneath surface at very deep depths. Field acquisition is often disturbed by the unwanted signal (known as noise) which originates from human activity, i.e. 50 Hz power line interference noise. The rejected noise in data processing will lead us to misinterpretation of earth's subsurface model. Consequently, the disturbed signal needs to be filtered on 50 Hz frequency. The chosen filter on this research is notch filter which is other form of stop-band filter. Notch filter has a narrow bandwidth so that can be approximated to a proper frequency value, which is 50 Hz. On the first step of filter designing, the sintetic signal with lower frequency than 50 Hz is applied to the designed filter and results show that filter successfully suppresses the 50 Hz noise. Magnetotelluric raw data is also applied and filter gives the same result of successfully suppressing the 50 Hz noise.